Business Ethics: Are Students Aware? A Cross Cultural Study of Three Nationalities - Agacer, Gilda M.; Valcarcel, Lina J.; Vehmanen, Petri (Philippine Management Review; Vol 4 (1993), 2016)
The basic question addressed in this study is whether business students, from three different countries located in three different continents, are aware of ethical conduct and if there are differences in awareness among these groups of students.  The subjects are from Mississippi State University (United States), the University of the Philippines (Philippines), and the University of Tampere (Finland).  Specifically, the study examines the students’ perception of ethical behaviour relative to sixteen cases, each of which describes an ethical dilemma.  The results show that, overall, the students from the three universities differed significantly in their perceptions of ethics.  The students from the University of the Philippines indicated the highest degree of ethical awareness whereas the students from the University of Tampere and the Mississippi State University showed almost identical scores.  In seven of the sixteen cases, the students clearly showed ethical awareness.  All three groups of students, however, were indifferent to situations that include training sales force on high-pressure selling techniques and giving awards to customers based on the value of purchases to maintain customer loyalty.  All three groups expressed strong disapproval of selling carcinogenic sleepwear in far flung areas where people have no means of knowing about the dangers of the product.